2021
DOI: 10.1212/wnl.0000000000011420
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Cervical Artery Dissection Among Hospitalized Patients With Stroke by Age in a Nationally Representative Sample From the United States

Abstract: Objective:To test the hypothesis that the prevalence of cervical artery dissection remains constant across age groups, we evaluated the relationship between age and cervical artery dissection in patients with stroke using a Nationally Representative Sample from the United States.Methods:We used inpatient claims data included in the 2012-2015 releases of the National Inpatient Sample (NIS). We used validated ICD-9-CM codes to identify adults hospitalized with ischemic stroke and a concomitant diagnosis of carot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
1
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 20 publications
0
15
1
1
Order By: Relevance
“…10 The incidence is slightly higher in men, 11 but the age at onset and the peak age prevalence of dissection-related stroke are lower in women (30-49 years) compared with men (50-89 years). 10,11 The pathogenesis of cervical artery dissection is multifactorial and involves the interplay of comorbidities, environmental triggers, genetic or congenital factors, including connective tissue disorders, and anatomic factors such as elongated styloid process (>30 mm; Eagle syndrome) or increased vascular tortuosity (Figure S1). 1,[12][13][14] Furthermore, risk factors may differ according to dissection location; recent systemic infection is more common in carotid artery dissection, and history of minor trauma is more common in vertebral artery dissection.…”
Section: Epidemiology/risk Factorsmentioning
confidence: 98%
“…10 The incidence is slightly higher in men, 11 but the age at onset and the peak age prevalence of dissection-related stroke are lower in women (30-49 years) compared with men (50-89 years). 10,11 The pathogenesis of cervical artery dissection is multifactorial and involves the interplay of comorbidities, environmental triggers, genetic or congenital factors, including connective tissue disorders, and anatomic factors such as elongated styloid process (>30 mm; Eagle syndrome) or increased vascular tortuosity (Figure S1). 1,[12][13][14] Furthermore, risk factors may differ according to dissection location; recent systemic infection is more common in carotid artery dissection, and history of minor trauma is more common in vertebral artery dissection.…”
Section: Epidemiology/risk Factorsmentioning
confidence: 98%
“…An interesting study utilizing nationwide inpatient data revealed that the prevalence of dissection among stroke hospitalizations was around 7% between age 18–40. 79
Figure 5 Right cervical internal carotid artery (ICA) dissecting pseudoaneurysm (white arrow) (reconstructed images from MRA) (figure on the left) and ipsilateral stroke on the ICA territory.
…”
Section: Immediate Complicationsmentioning
confidence: 99%
“…An interesting study utilizing nationwide inpatient data revealed that the prevalence of dissection among stroke hospitalizations was around 7% between age 18-40. 79 As with other ischemic strokes, the management of neurologic ischemic due to CeAD has two components: hyperacute treatment and secondary stroke prevention. The degree of luminal stenosis, presence of occlusion, intraluminal thrombus formation on the dissection sites, the amount of tissue at risk, and the intracranial extension of CeAD are essential factors.…”
Section: Tia/ischemic Strokementioning
confidence: 99%
“…A large epidemiologic study utilizing data from the National Inpatient Sample found that while CeAD accounted for a higher proportion of hospitalization for ischemic stroke in younger age groups, the actual prevalence of CeAD related stroke hospitalization increased with age. 21 As such, rigorous examination of the potential relationship between CSM and CeAD in older Medicare beneficiaries seems warranted. In this study, to better inform US policymakers, providers, and patients, we evaluated the association between CSM and CeAD among Medicare beneficiaries.…”
Section: Introductionmentioning
confidence: 99%